The Making of Gluten and Egg Free Cake from Composite Flour of Rice, Cassava, Potato Starch, and Soybean with The Addition of Hydrocolloid - Bosvin Abdalla Tambunan; Elisa Julianti; Ismed Suhaidi (Universitas Sumatera Utara, 2015)
The research was aimed to study the physical, chemical, and sensory characteristics of cake from composite flour of rice, cassava, potato starch, and soybean with the addition of hydrocolloid. This study used a completely randomized design with two factors, i.e : the proportion of rice flour: cassava flour : potato starch : soybean : xanthan gum in composite flour (T) : (30% : 50% : 15% : 4,5% : 0,5% ; 30% : 45% : 15% : 9,5% : 0,5% ; 30% : 40% : 15% : 14,5% : 0,5% and 100% wheat flour as control) and some type of egg replacer (G) : soy isolate protein, soy isolate protein : corn starch : guar gum and egg flour as control (36,4 g ; 24 g : 10,4 g : 2 g ; 36,4 g). The parameters analyzed were volume, browning index, texture, moisture content, ash content, protein content, fat content, carbohydrate content, crude fiber content, hedonic value of colour, aroma, flavor, and texture. The results showed that the ratio of rice flour, cassava flour, potato starch, soybean and xanthan gum had highly significant effect on volume, texture, moisture content, ash content, protein content, fat content, carbohydrate content, crude fiber content, hedonic value of colour, aroma, flavor, and texture. Type of egg replacer gave highly significant effect of the volume, browning index, protein content, fat content and carbohydrate content but had no significant effect on texture, moisture content, ash content, crude fiber content, hedonic value of colour, aroma, flavour and texture. Interaction of the two factors had highly significant effect on volume, browning index, fat content, and carbohydrate content. Proportion of rice, cassava, potato starch, soybean and xanthan gum (30% : 45% : 15% : 9,5% : 0,5) and soy isolate protein : corn starch : guar gum produced cake with the best quality. Keywords : cake, composite flour, egg free, egg replacer, gluten free